SETTLEMENT OF MEDICAL DISPUTES THROUGH LITIGATION AND NON-LITIGATION - Utama, Merry Sonia; Zamroni, Mohammad; Putera, Andika Persada (International Peneliti Ekonomi, Sosial dan Teknologi, 2024)
This study aims to analyse the settlement of medical disputes and legal protection for doctors in the event of a medical dispute based on Law No. 17 of 2023 concerning Health. This research uses normative juridical research with a statute approach and conceptual approach. The technique of collecting all legal materials used in this research is literature study and analysed using deductive logic data analysis techniques. Law enforcement officials are encouraged to prioritize restorative justice mechanisms to resolve disputes in accordance with Article 306 of the Health Law. Additionally, medical disputes that result in harm to patients should be prioritized for out-of-court settlement. The Health Law in Article 308 provides more specific provisions when the patient files a civil lawsuit and/or criminal charges; they must first obtain a recommendation issued by the council. Article 273 expressly accommodates aspects of legal protection for doctors and health workers, stating that medical and health workers, including doctors, in carrying out their practices are entitled to legal protection as long as they carry out their duties in accordance with professional standards, professional service standards, standard operational procedures, and professional ethics, as well as patient needs.